Disposable and low-cost electrochemical sensor based on the colorless nail polish and graphite composite material for tartrazine detection - de Lima, Lucas F.; Ferreira, André L.; Maciel, Cristiane C. [UNESP]; Ferreira, Marystela; de Araujo, William R. (Elsevier, 2021)
A new method to manufacture electrochemical devices based on the graphite and colorless nail polish (N-grap) film was developed for tartrazine (Tz) detection. Scanning Electron Microscopy (SEM) demonstrates that the composite material presents a high porous carbon structure. Cyclic voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS) were employed to electrochemically characterize the electrode material, which corroborates the porous structure of the N-graph due to the enhanced electroactive area (5.4-fold increase) and presented a heterogeneous electron transfer rate constant (k0) of 5.82 × 10−3 cm s−1 for potassium ferricyanide. The electrochemical determination of the Tz was carried out using square-wave voltammetry (SWV), under the optimized experimental conditions, which showed high sensitivity (0.793 A L mol−1) and a lower limit of detection (LOD) of 2.10 × 10−8 mol L−1 with a linear concentration ranging from 2.0 to 50.0 μmol L−1. The developed sensor was applied for the analysis of Tz in sports drink samples and the result obtained by N-grap device was statistically compared with a spectrophotometric method demonstrating good accordance and the accuracy of the proposed method. Based on these results, we believe that this new fabrication method to produce disposable and low-cost electrochemical devices can be an alternative method for in-field analysis of dye in commercial sport drink samples and other relevant applications.
Keywords: Composite material; Disposable sensor; Electrochemical sensor; Nail polish; Tartrazine